The fabrication of antibacterial composite from bacterial cellulose and betel leaves - Noor Izyannisa, Sarjuni (2010)
Wound healing was a complicated process that needs to be take care from infection and inflammation. Infection that occurs on wound will slow down the healing process. Therefore the objectives of this research were to produce antibacterial biocomposite from bacterial cellulose with betel leaves. The films were prepared by mixing the bacteria cellulose, betel leaves and gelatin in four different samples that contain from 0% to 70% composition of betel leaves extract. These biocomposite films were characterized by using Universal Testing Machine, Fourier Transform Infrared (FTIR) Spectroscopy, Scanning Electron Microscope (SEM), Gas Pycnometer, Antibacterial Effect Testing, water absorption testing and Biodegradable Testing. The biocomposite film that contains 70% Betel Leaves extract displayed better antibacterial properties, biodegradability and optimum water absorption for wound healing process. The film showed high effectiveness antibacterial activity towards gram positive bacteria rather than gram negative bacteria where the inhibition area was 0.20 cm2 and the effectiveness activity was 100%. There was about 343.87 mg/L of phenolic content in this sample. The film also showed the highest rate water absorption value which was 1.812 x 10-12 cm2/s and the film completely degraded in 24 days. The addition of betel leaves extracts and bacteria cellulose can be a promising source to produce biocomposite film that contains antibacterial effect which was suitable for wound healing and also can shorten the wound healing process.